2019
DOI: 10.1016/j.fct.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa intake attenuates renal injury in Zucker Diabetic fatty rats by improving glucose homeostasis

Abstract: Glucotoxicity (high levels of glucose) is a major factor in the pathogenesis of diabetic kidney disease. Cocoa has anti-diabetic effects by lowering glucose levels. However, whether cocoa exerts beneficial effects on the renal cortex glucose homeostasis and the molecular mechanisms responsible for this possible protective activity remain largely unknown. Thus, the potential anti-diabetic properties of cocoa on insulin signalling, glucose transporters and gluconeogenic enzymes were evaluated in the renal cortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Reports of SGLT1 protein [80,84,103] and mRNA [83-85, 92, 93, 98] contents in PTs of T1D murine models are also contradictory while in T2D models only mRNA expression seems to be upregulated [22,90,92,98,100,[103][104][105][106]. SGLT2 has been studied in many models of diabetes, and the results suggest increased protein [32,67,84,85,90,94,99,[107][108][109][110][111] and mRNA [22,32,83,85,100,104,[106][107][108][109]112] contents and activity [108] despite some controversial results [85,93,98,100,105,113].…”
Section: Tubular Glucose Transporters In Animal Models Ofmentioning
confidence: 99%
“…Reports of SGLT1 protein [80,84,103] and mRNA [83-85, 92, 93, 98] contents in PTs of T1D murine models are also contradictory while in T2D models only mRNA expression seems to be upregulated [22,90,92,98,100,[103][104][105][106]. SGLT2 has been studied in many models of diabetes, and the results suggest increased protein [32,67,84,85,90,94,99,[107][108][109][110][111] and mRNA [22,32,83,85,100,104,[106][107][108][109]112] contents and activity [108] despite some controversial results [85,93,98,100,105,113].…”
Section: Tubular Glucose Transporters In Animal Models Ofmentioning
confidence: 99%
“…This possibility was also indicated in the study conducted by Álvarez-Cilleros et al [30] where cocoa intake modified the gut bacterial composition towards a healthier profile of microbiota in diabetic rats [30]. The authors suggested that alterations in the gut microbiota improve glucose homeostasis and this phenomenon could be associated with the potential anti-obesity mechanisms of cocoa polyphenols include improvement glucose homeostasis and gut health [30,31].…”
Section: Resultsmentioning
confidence: 84%
“…Animal rodent models are considered useful tools for studying dietary obesity as they readily gain weight when fed high-fat diets [29]. Previous studies of animals and humans have suggested that cocoa intake could be related to the decreased risk of cardiovascular diseases, diabetes, and obesity [30][31][32][33][34][35][36][37][38][39]. Our recent study also showed that raw and roasted cocoa beans extracts (CBEs) as well as purified monomeric flavan-3-ols fraction isolated from them differently affected the activity of cecal enzymes and the content of volatile fatty acids in the gut but would not significantly affect the hematological parameters of rats fed a high-fat and low-fiber diet [40].…”
Section: Introductionmentioning
confidence: 99%
“…Such an effect could be the result of soluble fibers as well as flavonoids found in cocoa. 25,26 In addition, cocoa is rich in a number of saturated fatty acids, including palmitic acid and stearic acid, which may have contributed to increased serum TC and LDL-c levels. [27][28][29] Fig.…”
Section: Discussionmentioning
confidence: 99%